Changing from whole-cell to acellular pertussis vaccines would trade superior tolerability for inferior protection. (August 2015) - Herzog, Christian
<x xml:space="preserve">Abstract</x> Notifications of infant deaths, assumed to be related to the introduction of new pentavalent DTwP-Hib-HBV childhood vaccines, caused, during 2008–2010 in few Asian countries, temporary interruptions of the respective vaccination programs. The sudden appearance of fatal cases was due to increased awareness/publicity and improved safety monitoring/reporting in countries with relatively high background infant mortalities. WHO investigations could not establish any causal relationships and vaccinations were again resumed. Recently, questions were raised in one concerned country as to why not to change to less reactogenic acellular pertussis (aP)-containing vaccines that are available in private practice and are generally perceived as 'better'. For resource-poor countries, the financial impacts render such a switch impossible and would also not be supported by external funding. Furthermore, it would be a disservice to the children, as in recent years evidence of inferior long-term efficacy of aP vaccines has accumulated. This report summarizes current knowledge on comparative whole-cell pertussis (wP) and aP vaccine performance, outlines the new July 2014 WHO guidance on the choice of pertussis vaccines and presents recent data on outbreak protection, antibody waning, long-term protection, wP-priming, pathogen adaptation, transmission and herd immunity.